Evolutions of matter-wave bright soliton with spatially modulated nonlinearity - Cheng, Yongshan [UNESP]; Liu, Fei (Chinese Optics Letters Manuscript Office, 2009)
The evolution characteristics of a matter-wave bright soliton are investigated by means of the variational approach in the presence of spatially varying nonlinearity. It. is found that, the atom density envelope of the soliton is changed as a result of the spatial variation of the s-wave scattering length. The stable soliton can exist in appropriate initial conditions. The movement of the soliton depends on the sign and value of the coefficient of spatially modulated nonlinearity. These theoretical predictions are confirmed by the full numerical simulations of the one-dimensional Gross-Pitaevskii equation.